Smoking tends to decrease glutathione and increase malondialdehyde levels in medical students - Safyudin, Safyudin; Subandrate, Subandrate (Universa Medicina, 2016)
BackgroundSmoking is the act of introducing toxic substances into the body. Cigarette smoke contains chemicals that may cause several disorders, including cardiovascular disease, cancer, and chronic obstructive pulmonary disease. Toxic substances in cigarette smoke have the potential to increase free radicals, malondialdehyde (MDA) levels and to decrease endogenous antioxidant (glutathione/GSH) levels. This study aims to determine the relationship of smoking with plasma GSH and MDA levels in medical students.MethodsThis study was analytical observational with cross-sectional approach. The study was conducted from April to December 2015. The subjects in this study were medical students, consisting of 20 smokers and 20 nonsmokers. Plasma GSH and MDA levels were determined biochemically using Sigma GSH Assay Kit and Sigma MDA Assay Kit. Data was analyzed using the independent t test. ResultsThe results showed that there was no significant difference between mean GSH in smokers (1.74 ± 0.91 mmol/L) and nonsmokers (2.42 ± 1.19 µmol/L) (p=0.441). Mean smokers MDA level of 2.06 ± 1.39 nmol/mL was not significantly different compared with mean nonsmokers MDA level (1.32 ± 0.90 nmol/mL) (p=0.092).ConclusionsSmoking tends to decrease plasma GSH levels and increase plasma MDA levels in medical students. Smoking history could be evidence of oxidative stress and an impaired oxidant defense system. In particular, young smokers should quit promptly before health problems arise, so as to have the optimal benefits of cessation.